Heat stress during male meiosis impairs cytoskeletal organization, spindle assembly and tapetum degeneration in wheat - Fábián, Attila; Péntek, Barbara Krárné; Soós, Vilmos; Sági, László (Frontiers in Plant Science, 2024)
The significance of heat stress in agriculture is ever-increasing with the progress of global climate changes. Due to a negative effect on the yield of staple crops, including wheat, the impairment of plant reproductive development triggered by high ambient temperature became a restraint in food production. Although the heat sensitivity of male meiosis and the following gamete development in wheat has long been recognized, a detailed structural characterization combined with a comprehensive gene expression analysis has not been done about this phenomenon. We demonstrate here that heat stress severely alters the cytoskeletal configuration, triggers the failure of meiotic division in wheat. Moreover, it changes the expression of genes related to gamete development in male meiocytes and the tapetum layer in a genotype-dependent manner. 'Ellvis', a heat-tolerant winter wheat cultivar, showed high spikelet fertility rate and only scarce structural aberrations upon exposure to high temperature.In addition, heat shock genes and genes involved in scavenging reactive oxygen species were significantly upregulated in 'Ellvis', and the expression of meiosis-specific and major developmental genes showed high stability in this cultivar. In the heat-sensitive 'Mv 17-09', however, genes participating in cytoskeletal fiber nucleation, the spindle assembly checkpoint genes, and tapetum-specific developmental regulators were downregulated. These alterations may be related to the decreased cytoskeleton content, frequent micronuclei formation, and the erroneous persistence of the tapetum layer observed in the sensitive genotype. Our results suggest that understanding the heat-sensitive regulation of these gene functions would be an essential contribution to the development of new, heat-tolerant cultivars.